Health and Production Performance of Broiler strain Cobb with Closed House IoT system in Cimahpar, Bogor - Arif, Ridi; Widiatmoko, Agus; Nurzuliana, Dina (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2024)
One source of affordable protein for the Indonesian was broiler chickens. Farmer were competing to do optimal broiler production. For independent farmers, it is difficult to carry out efficient production because of global warming which triggers rapidly changing microclimate condition. Therefore, the closed house system can be an alternative. The purpose of this study was to observe the performance of strain cobb broilers reared in a closed house system supported by the Internet of Things (IoT). A total of 12,000 DOC were divided into 2 types of cages and 2 maintenance periods. The types of cages used were closed and open house and the maintenance period was January-February and April-May 2022. Each cage contain of 3,000 individuals and were maintained with a standard system. IoT systems were used to monitor the microclimate conditions. The results of the recording show that the closed house system gives better results. The comparison of the average body weight per chicken between closed and open house on days 4, 15, 25, and 30 respectively was 88 and 86 g; 520 and 495 gr; 1.73 gr and 1.127; 1,630 and 1,520 gr. The total harvest weight gave an increase of 5.21% (4,259 to 4,481.8 kg) and a better FCR from 1.49 to 1.40 in the closed house system. The closed house system for independent farmer was able to increase the efficiency because it provides comfortable microclimate so that the chickens grow better. The independent farmers can use closed house system for more profitable broiler production.